2018
DOI: 10.1016/j.matdes.2018.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of axial plastic zone for roller bearing overloads using neutron transmission imaging

Abstract: Article HIGHLIGHTS• A loading frame was designed to simulate bearing overloads on the ENGIN-X strain diffractometer at ISIS neutron source, UK.• Neutron transmission imaging was used to map a Bragg edge fitting parameter, associated with material yielding.• It was demonstrated that bearing overloads generate regions of subsurface plasticity in overloaded roller bearings.• Subsurface deformation, observed during roller bearing overload events, appears to reduce the bearings life expectancy. Premature failure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Radiography has been also employed in bearings. Reid et al [86] have proposed the images from the Neutron Bragg edge to obtain two-dimensional mapping to detect the plastic deformation. The results showed that there is a strong correlation between the load and the width of the Bragg rim.…”
Section: Radiographic Testingmentioning
confidence: 99%
“…Radiography has been also employed in bearings. Reid et al [86] have proposed the images from the Neutron Bragg edge to obtain two-dimensional mapping to detect the plastic deformation. The results showed that there is a strong correlation between the load and the width of the Bragg rim.…”
Section: Radiographic Testingmentioning
confidence: 99%
“…Further development will be undertaken by the author to fully integrate Windows OS, making the software a cross-platform code. BEATRIX has already been used in a number of scientific studies (Vitucci et al, 2018;Kockelmann et al, 2018;Reid et al, 2018;Ramadhan et al, 2019), and this manuscript provides a useful introduction to the capabilities of this software tool. Moreover, a short illustration of BEATRIX is provided here for a typical data analysis of an energy-resolved imaging experiment.…”
Section: Motivation and Featuresmentioning
confidence: 99%
“…As a result of the strong coherent elastic scattering interaction for thermal and cold neutrons, the measured transmission pattern contains important information about the crystalline state of the specimen. In particular, precise determination of the positions of Bragg edges provides a measure of lattice parameters (Santisteban et al, 2001(Santisteban et al, , 2002aSantisteban, 2005;Malamud & Santisteban, 2016;Tremsin et al, 2016;Ramadhan et al, 2018Ramadhan et al, , 2019Reid et al, 2018), while the heights of these edges give information about phase volume fractions (Steuwer et al, 2005;Woracek et al, 2014) and texture effects (Kockelmann et al, 2007;Santisteban et al, 2012;Malamud et al, 2014;Sato et al, 2017). The neutron wavelength shown in equation 3is a variable that is not directly measurable, and its value is usually determined at a pulsed neutron source via determination of the time of flight (TOF) for neutrons propagating at constant velocity along the instrument flight path.…”
Section: Introductionmentioning
confidence: 99%
“…The neutron Bragg-edge transmission imaging method, in which diffraction analysis is performed using neutron transmission, has been employed in several studies to nondestructively visualize the residual strain distribution inside bulk metallic materials. [18][19][20][21][22][23][24] The wavelength of neutrons can be determined with high accuracy using the time-of-flight (TOF) technique with a pulsed neutron beam. [21][22][23] The neutron transmission spectrum can be obtained pixel by pixel using a 2D and time-resolving detector.…”
Section: Introductionmentioning
confidence: 99%